2003
DOI: 10.3354/meps258003
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular enzyme activity and uptake of carbon and nitrogen along an estuarine salinity and nutrient gradient

Abstract: Amino acid oxidation (AAO) and peptide hydrolysis (PH) are processes affecting the recycling of organic material and nutrients. We compared extracellular AAO and PH rates to C and N uptake rates along estuarine gradients of salinity, nutrients and productivity in the Pocomoke River, a subestuary of the Chesapeake Bay. This estuary is seasonally depleted in inorganic N, and rich in dissolved organic material (DOM) throughout the year. AAO, PH, and N uptake rates measured in 1999 and 2000 were not limited to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…The phyto C: phyto N ratios of the HAAs at this station demonstrate preferential phyto N incorporation by the bacteria, at this station. Previous studies emphasise the importance of extracellular amino-acid oxidation as a pathway for N incorporation in marine systems (Pantoja and Lee, 1994;Mulholland et al, 2003;Veuger and Middelburg, 2007). In the extracellular amino-acid oxidation pathway bacteria liberate NH 4 þ from amino acids outside their cell walls (Pantoja and Lee, 1994).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The phyto C: phyto N ratios of the HAAs at this station demonstrate preferential phyto N incorporation by the bacteria, at this station. Previous studies emphasise the importance of extracellular amino-acid oxidation as a pathway for N incorporation in marine systems (Pantoja and Lee, 1994;Mulholland et al, 2003;Veuger and Middelburg, 2007). In the extracellular amino-acid oxidation pathway bacteria liberate NH 4 þ from amino acids outside their cell walls (Pantoja and Lee, 1994).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The uptake of DON by phytoplankton is poorly understood (Mulholland et al, 2003) so we set the half saturation constant for uptake by phytoplankton at 20 M, which allows phytoplankton to take up some DON but restricts it from being their dominant nitrogen source. Phytoplankton use DIC in combination with nutrients at a fixed C:N ratio for production (Anderson and Pondaven, 2003).…”
Section: Phytoplanktonmentioning
confidence: 99%
“…This formulation allows phytoplankton cells to take up ammonium and labile DON preferentially, with nitrate uptake inhibited in the presence of significant concentrations of ammonium Harrison et al, 1996) and labile DON. DON uptake by phytoplankton was included in this model because recent research has shown that DON can be a significant nitrogen source (up to 50%) for phytoplankton (Fan et al, 2003;Mulholland et al, 2002Mulholland et al, , 2003. The maximum attainable daily growth rate of large phytoplankton, P , was calculated using an exponential temperature function (Bissinger et al, 2008;Eppley, 1972).…”
Section: Phytoplanktonmentioning
confidence: 99%
See 2 more Smart Citations